Uma avaliação sobre a qualidade dos serviços prestados pela construção civil em empreendimentos residenciais de médio e alto padrão em Maringá-PR - Carneiro, Rafaela Cardoso Galace (2020)
The civil construction sector is among the ones that most felt, and still is feeling, the turnouts of the Brazilian economics crisis; although that this is the best scenario for opportunities and growth. Besides the bad economic performance, civil construction shows itself as one of the less innovative industries, what justifies the interest in measuring and managing the quality of the services it provides, to systemize the companies processes aiming the customer satisfaction. Managing tools has been widely used in the search for quality in productive processes, provided services and in the product itself, because total quality has been the industries focus for a very long time. As civil construction has the crucial role in the future of the country economy, among other initiatives, the sector must start measure its services and the Servqual scale is considered a big ally, because it is a research model that exist to measure the quality. In this scale the client values, according to his perception, the service provided by a company based on his initial expectations. Given the above, this study presents an analyze quali-quantitative, that helped to characterize and construct a profile of an medium and high standard residential real estate developments costumer in the city of Maringá, on the interior of Paraná state. Descriptive statists and five dimensions Servqual scale were used taking in consideration the importance of each one of them. In the extraction of three dimensions through factor analysis, 16 of the 24 questions were grouped considering a correlation greater than 70%. As a final result it was possible to verify that the costumers would like to be attended with polite by the company that his going to acquire the services from, add to that the flexibility with what the company should take possible projects adjustments. When it comes to perception on realization of the acquired services, there were highlights on the fact that the company had an team that inspires trust, proactivity in dealing the costumer matters, and always available, therefore achieving the ideal quality, in expectative as in experience. Also relevant to the individual analysis of each company that showed results that succeed expectation in some cases and greater discrepancies in others. It is suggested, for future references,the managing of implementing a project in Servqual methodology for continuous measuring the quality in civil construction companies. It is concluded that the objectives were achieved, the profile of the focus customer of the research was drawn and the companies were evaluated and it was possible to contribute with them to implement an improvement plan.